High-CO2 Levels Rather than Acidification Restrict Emiliania huxleyi Growth and Performance - Vázquez Manzanares, Víctor; León Díaz, Pablo Ignacio; López-Gordillo, Francisco Javier; Jiménez, Carlos; Íñiguez Moreno, Concepción; MacKenzie, Kevin; Bresnan, Eileen; Segovia-Azcorra, María (Springer, 2022)
The coccolithophore Emiliania huxleyi shows a variety of responses to ocean acidification (OA) and to high-CO2 concentrations, but there is still controversy on differentiating between these two factors when using different strains and culture methods. A heavily calcified type A strain isolated from the Norwegian Sea was selected and batch cultured in order to understand whether acclimation to OA was mediated mainly by CO2 or H+, and how it impacted cell growth performance, calcification, and physiological stress management. Emiliania huxleyi responded differently to each acidification method. CO2-enriched aeration (1200 µatm, pH 7.62) induced a negative effect on the cells when compared to acidification caused by decreasing pH alone (pH 7.60). The growth rates of the coccolithophore were more negatively affected by high pCO2 than by low pH without CO2 enrichment with respect to the control (400 µatm, pH 8.1). High CO2 also affected cell viability and promoted the accumulation of reactive oxygen species (ROS), which was not observed under low pH. This suggests a possible metabolic imbalance induced by high CO2 alone. In contrast, the affinity for carbon uptake was negatively affected by both low pH and high CO2. Photochemistry was only marginally affected by either acidification method when analysed by PAM fluorometry. The POC and PIC cellular quotas and the PIC:POC ratio shifted along the different phases of the cultures; consequently, calcification did not follow the same pattern observed in cell stress and growth performance. Specifically, acidification by HCl addition caused a higher proportion of severely deformed coccoliths, than CO2 enrichment. These results highlight the capacity of CO2 rather than acidification itself to generate metabolic stress, not reducing calcification.
Keywords: Calcificación; Emiliania huxleyi; Ocean acidifcation; Calcifcation; pCO2; Photochemistry; Phytoplankton; Stress; Coccolithophores